Site Suitability Analysis for Landfill in an Industrial Area in Nigeria - Olayiwola, Adewale; Suleiman, Umar (Journal of Environmental Geography, 2022)
This study was set against the background of identifying management strategies to combat the menace associated with poor solid waste management in urban areas of Nigeria. Therefore, it becomes highly necessary to determine suitable sites for landfill. Using remote sensing and geographic information tools and technologies the study identified the scenes of present dump sites; evaluated the conditions for selecting landfill sites; and determined suitable landfills in Ajaokuta, Nigeria. Data for the study were sourced from Sentinel-2A, 2021. Integrated GIS-based analysis using multi-criteria evaluation method was employed to scrutinise the appropriateness of the existing dumpsites for siting landfills. However, with reference to Federal Environmental Protection Agency (FEPA) guidelines, results of buffering and proximity analyses indicated that none of the existing dumpsites could be converted to landfill sites. Moreover, a fuzzy overlay of all the criteria considered was employed to identify and propose the most suitable areas for solid waste disposal sites in the study area. Based on the official stipulated distance, new sites were proposed for landfills. The study emphasised the increasing mounds and improper disposal of municipal solid wastes in Nigerian urban centres which have become too agonising and repulsive to sights. Nevertheless, if the recommendations of this study are taken with utmost seriousness, any unexpected outbreak of epidemic and environmental pollution will be greatly avoided in the study area.